Integrability conditions for SDEs and semilinear SPDEs - Feng-yu Wang (The Annals of Probability, 2017)
By using the local dimension-free Harnack inequality established on incompleteRiemannian manifolds, integrability conditions on the coecients are presented forSDEs to imply the non-explosion of solutions as well as the existence, uniqueness andregularity estimates of invariant probability measures. These conditions include a classof drifts unbounded on compact domains such that the usual Lyapunov conditions cannot be veried. The main results are extended to second order dierential operatorson Hilbert spaces and semi-linear SPDEs.